Depresi Pada Pasien dengan Penyakit Jantung Koroner yang mengalami Left Ventricular Ejection Fraction Rendah : A Scoping Review - Dirman Abdullah; Anastasia Anna; Aan Nuraeni (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Depression is one of the most common psychological comorbidities in patients with coronary heart disease, but research on patients with low left ventricular ejection fraction remains limited. This condition can worsen clinical prognosis and reduce patients' quality of life. This review aims to identify depression in coronary heart disease patients with low left ventricular ejection fraction. This study used a scoping review design. Literature searches were conducted in three main databases, namely EBSCOhost, PubMed, and ScienceDirect, as well as one additional search engine, Google Scholar. The keywords used included: “coronary heart disease OR myocardial infarction OR acute coronary syndromes OR unstable angina AND Low Left Ventricular Ejection Fraction OR Low LVEF AND Depression”. Inclusion criteria included: (1) studies involving patients with coronary heart disease, (2) studies evaluating the relationship between left ventricular ejection fraction and symptoms of depression, and (3) publications in English or Indonesian. Data analysis was performed using descriptive qualitative methods. A total of 707 studies were found in the literature search, which were then selected based on their titles and abstracts. A total of 7 out of 707 articles were analyzed in this review. Four of the seven studies reported that low left ventricular ejection fraction was associated with increased symptoms of depression in patients with coronary heart disease, especially after myocardial infarction. Meanwhile, the other two studies stated that there was no direct relationship but rather the influence of other factors such as social support and psychological history. Depression is a common condition in patients with coronary heart disease. Patients with coronary heart disease with low left ventricular ejection fraction are closely related to an increased risk of depression in CHD patients, and both worsen the clinical prognosis. Early detection and integrated management of depression are crucial for improving patients' quality of life and cardiovascular outcomes. A comprehensive approach encompassing pharmacological and psychosocial interventions has proven to be the most effective strategy for addressing depression in CHD patients. Keywords: Depression, Low Left Ventricular Ejection Fraction, Coronary Heart Disease.  ABSTRAK Depresi merupakan salah satu komorbid psikologis yang umum terjadi pada pasien dengan penyakit jantung koroner, namun penelitian pada pasien dengan left ventricular ejection fraction rendah masih sangat terbatas. Kondisi ini dapat memperburuk prognosis klinis dan menurunkan kualitas hidup pasien. Review ini bertujuan untuk mengidentifikasi depresi pada pasien penyakit jantung koroner yang mengalami left ventricular ejection fraction rendah. Studi ini menggunakan desain scoping review. Pencarian literatur dilakukan pada tiga database utama, yaitu EBSCOhost, PubMed, dan ScienceDirect, serta satu mesin pencari tambahan, Google Scholar. Kata kunci yang digunakan mencakup: “coronary heart disease OR myocardial infarction OR acute coronary syndromes OR unstable angina AND Low Left Ventricular Ejection Fraction OR Low LVEF AND Depression”. Kriteria inklusi meliputi: (1) studi yang melibatkan pasien dengan penyakit jantung koroner, (2) studi yang mengevaluasi hubungan antara left ventricular ejection fraction dan gejala depresi, serta (3) publikasi dalam bahasa Inggris atau Indonesia. Analisis data dilakukan secara deskriptif kualitatif. Pencarian literature didapatkan total sebanyak 707 studi yang kemudian diseleksi judul dan abstrak. Sebanyak 7 dari 707 artikel  dianalisis pada review ini. 4 dari 7 studi melaporkan bahwa left ventricular ejection fraction rendah berhubungan dengan meningkatnya gejala depresi pada pasien penyakit jantung koroner, terutama pasca-infark miokard. Sedangkan, dua studi lainnya menyatakan tidak adanya hubungan langsung melainkan pengaruh faktor lain seperti dukungan sosial dan riwayat psikologis. Depresi merupakan kondisi yang umum terjadi pada pasien penyakit jantung koroner. Pasien penyakit jantung koroner dengan tingkat left ventricular ejection fraction rendah berkaitan erat dengan peningkatan risiko depresi pada pasien PJK, dan keduanya saling memperburuk prognosis klinis. Deteksi dini dan manajemen depresi secara terintegrasi sangat penting untuk meningkatkan kualitas hidup dan hasil kardiovaskular pasien. Pendekatan komprehensif yang mencakup intervensi farmakologis dan psikososial terbukti menjadi strategi yang paling efektif dalam mengatasi depresi pada pasien PJK. Kata Kunci: Depresi, Left Ventricular Ejection Fraction Rendah, Penyakit Jantung Koroner.